Structure and function of neocortical layer 6b - Feldmeyer, Dirk (Frontiers in Cellular Neuroscience, 2023)
Cortical layer 6b is considered by many to be a remnant of the subplate that forms during early stages of neocortical development, but its role in the adult is not well understood. Its neuronal complement has only recently become the subject of systematic studies, and its axonal projections and synaptic input structures have remained largely unexplored despite decades of research into neocortical function. In recent years, however, layer 6b (L6b) has attracted increasing attention and its functional role is beginning to be elucidated. In this review, I will attempt to provide an overview of what is currently known about the excitatory and inhibitory neurons in this layer, their pre-and postsynaptic connectivity, and their functional implications. Similarities and differences between different cortical areas will be highlighted. Finally, layer 6b neurons are highly responsive to several neuropeptides such as orexin/hypocretin, neurotensin and cholecystokinin, in some cases exclusively. They are also strongly controlled by neurotransmitters such as acetylcholine and norepinephrine. The interaction of these neuromodulators with L6b microcircuitry and its functional consequences will also be discussed.of